2011
DOI: 10.4315/0362-028x.jfp-10-398
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Behavior of Salmonella and Escherichia coli on Whole and Sliced Jalapeño and Serrano Peppers

Abstract: The frequencies of coliform bacteria (CB), thermotolerant coliforms (TC), Escherichia coli, and Salmonella were determined for jalapeño and serrano peppers. In addition, the behavior of four serotypes of Salmonella and three E. coli strains on whole and sliced jalapeño and serrano peppers as well as in blended sauce at 25 ± 2°C and 3 to 5°C was investigated. Chili peppers were collected from markets in the city of Pachuca, Hidalgo, Mexico. CB, TC, E. coli, and Salmonella were detected on serrano peppers in 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
4
22
1
Order By: Relevance
“…Populations of E. coli and Salmonella declined at both 4 and 25°C over 6 days in a study by Castro-Rosas et al (10). In contrast to our study and those mentioned above, another study found that populations of S. enterica did not change when introduced to the surface of jalapeno peppers and held at 4 and 12°C for 1 week (30).…”
Section: Discussioncontrasting
confidence: 89%
“…Populations of E. coli and Salmonella declined at both 4 and 25°C over 6 days in a study by Castro-Rosas et al (10). In contrast to our study and those mentioned above, another study found that populations of S. enterica did not change when introduced to the surface of jalapeno peppers and held at 4 and 12°C for 1 week (30).…”
Section: Discussioncontrasting
confidence: 89%
“…Wounding has generally been observed to increase the numbers of E. coli retained by plant tissues (Brandl, ; Harapas et al ., ; Castro‐Rosas et al ., ). We also observed that wounding increased retention of E. coli by leaves and fruits.…”
Section: Discussionmentioning
confidence: 97%
“…Retention of E. coli O157 by cut leaves and fruits has generally been observed to be rapid occurring within hours of exposure of the leaves or fruits to the bacteria (Brandl, ; Castro‐Rosas et al ., 2010; 2011; Harapas et al ., ; Tian et al ., ). We observed that cut leaves of lettuce, spinach, alfalfa, bean and A. thaliana retained significant numbers of bacteria within the first 5 min of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Castro-Rosas et al (2011) detected Salmonella on 12% and 10% of jalapeñ o and serrano peppers, respectively, obtained from the markets in a city of Mexico. However, data from the same report showed significant reduction of experimentally inoculated Salmonella (Salmonella Typhi, Montevideo, Gaminara, or Typhimurium) on the peppers during humid storage at 25°C for 6 days.…”
Section: Discussionmentioning
confidence: 99%